Effective field theory investigations of the XYZ puzzle. (August 2016) - Segovia, Jorge
Abstract: Quantum Chromodynamics, the theory of strong interactions, predicts several types of bound states. Among them are conventional mesons ( qq̅ ) and baryons ( qqq ), which have been the only states observed in experiments for years. However, in the last decade, many states that do not fit this picture have been observed at B -factories (BaBar, Belle and CLEO), at τ-charm facilities (CLEO-c, BESIII) and also at proton-proton colliders (CDF, D0, LHCb, ATLAS, CMS). There is growing evidence that at least some of the new charmonium- and bottomonium-like states, the so-called XYZ mesons, are new forms of matter such as quark-gluon hybrids, mesonic molecules or different arrangements of tetraquarks, pentaquarks... Effective Field Theories (EFTs) have been constructed for heavy-quark-antiquark bound states, but a general study of the XYZ mesons within the same framework has not yet been done. The scope of this conference proceedings is to discuss the possibilities we have in developing novel EFTs that, characterizing the conventional quarkonium states, facilitate also the systematic and model-independent description of the new exotic matter, in particular, the hybrid mesons.